Case report: A case of Acute Macular Neuroretinopathy secondary to Influenza A virus during Long COVID - Zhang, Jiaqi; Xia, Yihao; Li, Xiaodong; He, Runxi; Xie, Xuejun (Frontiers in Immunology, 2024)
Ocular abnormalities have been reported in association with the virus infections and Long COVID, the debilitating illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here, we report a case of a female patient diagnosed with acute macular neuroretinopathy (AMN) after infecting influenza A during Long COVID, who had severe inflammation symptoms and ocular complications. We speculate that the rare AMN symptom in the patient could relate to the immune storm secondary to virus infection during Long COVID.